If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4y + z = 0 Solving 2x + -4y + z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 2x + -4y + 4y + z = 0 + 4y Combine like terms: -4y + 4y = 0 2x + 0 + z = 0 + 4y 2x + z = 0 + 4y Remove the zero: 2x + z = 4y Add '-1z' to each side of the equation. 2x + z + -1z = 4y + -1z Combine like terms: z + -1z = 0 2x + 0 = 4y + -1z 2x = 4y + -1z Divide each side by '2'. x = 2y + -0.5z Simplifying x = 2y + -0.5z
| 8(2z-5)=4n+8 | | 3-8+2x=11+6x | | p/20=8/4 | | [-2+6x]+3=59 | | 5.79x-3.14y=-13.54 | | 3(2-0.9q)+(-1.3h-4)= | | -3(4t-4)+6t=5t-9 | | x^2+8+14=0 | | 4x-10+2x=8 | | f+g=f+h | | x^2+814=0 | | x^2+8+14= | | 6-(-5r)=5r+6 | | -8x+32-5=-5-9x | | sec(x)sin(x)-2sin(x)=0 | | 4x-32+20=5 | | 3*x+2-8=3*x | | sex(x)sin(x)-2sin(x)=0 | | 12.50+0.15t=20 | | X^2+10x+52=0 | | 9d-d+d-5-6d=0 | | 5xy+9y^4=8x^4+3y | | 30+2x=5 | | 12-7*x+x^2=0 | | -5(3t-5)+3t=5t-8 | | Q=4n+4q | | 23+n=87 | | X+2x+(x+30)=102 | | -3(x+3)=-3x-9 | | (4v-3)(v+5)=0 | | -8x-9-3x+2=1 | | 3(4x+40)=360 |